Sharia Marketing Strategy Using SWOT Analysis At PT. Yotta Berkah Mulia - Rafika Nur Isna; Rahman Ambo Masse; A Syathir Sofyan; Rahmawati Muin; Muslihati Muslihati (Borneo Islamic Finance and Economics Journal, 2026)
This study aims to examine the implementation of sharia marketing strategies at PT. Yotta Berkah Mulia by utilizing SWOT analysis as a strategic evaluation tool. The research adopted a descriptive qualitative approach, with data collected through observation, interviews, questionnaires, and documentation. The findings show that PT. Yotta Berkah Mulia has successfully applied the four fundamental characteristics of sharia marketing, namely Theistic (Rabbaniyyah), Ethical (Akhlaqiyyah), Realistic (Al-Waqi’iyyah), and Humanistic (Al-Insaniyyah), in its marketing activities. The SWOT analysis was conducted to identify the company’s strengths, weaknesses, opportunities, and threats. Based on the results of the IFAS and EFAS matrices, the company is positioned in Quadrant II, indicating that it possesses strong internal capabilities despite facing several external challenges and threats. This position suggests that a diversification strategy is the most appropriate approach to maintain competitiveness and support future business growth. Furthermore, the results of this study are expected to contribute to the development of sharia-based marketing practices and serve as a reference for MSMEs in formulating more effective, adaptive, and sustainable marketing strategies.